The Views of Nahdlatul Ulama and Muhammadiyah Figures on Credit Transactions with a Savings System - Al Munawar, Faishal Agil; Vad'aq, M. Iqbal (Indonesian Journal of Islamic Economics and Finance, 2024)
As practiced by @dintwinz_home on Instagram, credit buying with a savings system offers a unique approach to transactions compared to conventional methods. Unlike typical credit purchases, this method allows buyers flexibility with payment deadlines and amounts. Customers can cancel purchases and withdraw their installment funds. This empirical study adopts a qualitative approach, utilizing interviews and documentation to explore the perspectives of Nahdlatul Ulama (NU) and Muhammadiyah figures in Malang City. Key findings include the structured stages of this buying process: (1) visiting @dintwinz_home; (2) item specification and purchase explanation; (3) initial down payment and identity submission; (4) installment recording by the seller; (5) withdrawal of saved funds if needed; and (6) item delivery upon completion. The study highlights disagreement among Muhammadiyah figures due to a perceived lack of payment clarity, whereas NU figures support the practice under mutual agreement conditions. This research provides insights into community perspectives on evolving transaction practices in digital commerce.